2007
DOI: 10.1016/j.yjmcc.2006.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent hypoxia-induced delayed cardioprotection is mediated by PKC and triggered by p38 MAP kinase and Erk1/2

Abstract: . Intermittent hypoxia-induced delayed cardioprotection is mediated by PKC and triggered by p38 MAP kinase and Erk1/2.. Journal of Molecular and Cellular Cardiology, Elsevier, 2007, 42 (2) AbstractObjective. We previously reported that acute intermittent hypoxia (IH) confers delayed cardioprotection against a prolonged ischemic insult in the rat, via the involvement of nitric oxide synthase and K ATP channels. In the present study, we investigated the role of protein kinase C (PKC), phosphatidylinositol-3-ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 40 publications
3
34
0
1
Order By: Relevance
“…When this occurs, renal cells initially respond with protective mechanisms that center around the phosphorylation of extracellular signal-regulated protein kinases 1 and 2 and the resulting stabilization of both HIF-1α and HIF-2α. [94][95][96]292,[323][324][325] These protective mechanisms include the up-regulation of pro-angiogenic factors such as isoform 164 of VEGF-A that protect against capillary rarefaction, and increased expression of matrix metalloproteinases that effect repair and protect against fibrosis by degrading extracellular matrix. 326,327 In addition, short-term exposure to hypoxia leads to increased renal expression of antioxidants such as nuclear factor erythroid 2-related factor 2, hemeoxygenase 1, and metallothionein I that protect against fibrosis and inflammation induced by reactive oxygen species.…”
Section: The Hypoxia Death Cyclementioning
confidence: 99%
“…When this occurs, renal cells initially respond with protective mechanisms that center around the phosphorylation of extracellular signal-regulated protein kinases 1 and 2 and the resulting stabilization of both HIF-1α and HIF-2α. [94][95][96]292,[323][324][325] These protective mechanisms include the up-regulation of pro-angiogenic factors such as isoform 164 of VEGF-A that protect against capillary rarefaction, and increased expression of matrix metalloproteinases that effect repair and protect against fibrosis by degrading extracellular matrix. 326,327 In addition, short-term exposure to hypoxia leads to increased renal expression of antioxidants such as nuclear factor erythroid 2-related factor 2, hemeoxygenase 1, and metallothionein I that protect against fibrosis and inflammation induced by reactive oxygen species.…”
Section: The Hypoxia Death Cyclementioning
confidence: 99%
“…It has been suggested that alteration in long-term facilitation and hypoxic ventilatory response in reply to intermittent hypoxia exposure could lead to breathing stability and reduction in apnoea/hypopnoea index, although this is still conflicting [22]. There are also potential beneficial effects with regard to cardiovascular consequences that have been suggested in animals exposed to intermittent hypoxia [23][24][25]. This might also be the case in OSA with respect to vascular adaptations [26,27] and possibly lower mortality [16].…”
Section: Basic Mechanisms Linking Osa and Cardiovascular Diseasesmentioning
confidence: 99%
“…Moderate chronic intermittent hypobaric hypoxia (CIHH), similar to ischemic preconditioning and long-term adaptation to high-altitude hypoxia, protects the heart against I/R injury [9,10,11,12]. This CIHH-induced cardiac protection persists longer than ischemic preconditioning [13,14] and is associated with less side effects on the body, such as polycythemia, right ventricular hypertrophy and pulmonary hypertension compared with long-term adaptation to high-altitude hypoxia [15,16,17].…”
Section: Introductionmentioning
confidence: 99%